Optimizing the Utilization of Fermented Natural Materials as Mosquito Trapping Attractives - Saputra, Roni; Gemala, Mega; Oktarizal, Hengky; Dewita, Trisna; Rahmayni, Wanda (Universitas Mandala Waluya, 2022)
Mosquitoes are insects that can interfere because, in addition to causing itching and pain, several types of mosquitoes are vectors or transmitters of various diseases. One of the free and environmentally friendly mosquito vector controls is to make simple traps with attractants containing fermented natural ingredients. This study aimed to determine the effectiveness of cassava fermentation, sugarcane water fermentation, brown sugar fermentation, and banana skin fermentation as mosquito attractants. This study is experimental research designed as a post-test–only control group design. The results showed that the ability of fermented cassava, sugarcane water fermentation, brown sugar fermentation as mosquito attractants did not significantly differ in attracting mosquitoes with the number of trapped mosquitoes was 62 tails, 56 tails, 50 were seen during nine days of research. Whereas for banana peel fermentation with the number of mosquitoes trapped 27 seats which were seen for nine research days and experienced a decrease from day to day. These results show that cassava fermentation is the most effective as the attractant of mosquitoes, with the number of mosquitoes trapped during nine days of research 62 tails, with an average of trapped mosquitoes as many as three and effective on day 5 of the study.